2017
DOI: 10.1021/acs.cgd.7b00806
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Recrystallization of Tubular Vinpocetine Crystals with Increased Aqueous Dissolution Rate and In Vivo Bioavailability

Abstract: Vinpocetine was a BCS II drug, whose clinical applications had suffered from low oral bioavailability because of its inefficient dissolution in the GI tract. As the dissolution rate depended on the surface area of the drug crystals, we herein explored shape-controlled recrystallization via antisolvent process as an excipient-free strategy to improve the bioavailability of VIN. By adjusting the water/ethanol ratio, initial VIN concentration, and temperatures, morphologies of the crystalline products could be fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The crystal surface condition of the VIP crystal and the presence of cavities could be obtained by scanning electron microscopy (SEM) analysis. A crystal habit regulation scheme for hollow tubular VIP crystal has been reported by Sun et al 15 The SEM photographs shown in Figure 6 revealed a cubic VIP crystal with multiple types of cavities on the surface of the crystal. These features shared by Figure 6a,b suggested that the isolated cavities on the crystal plane usually appear at the junction of the crystal face, and the scanning electron microscope image shows that the size of the exposed cavities entrance reached 10−20 μm.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The crystal surface condition of the VIP crystal and the presence of cavities could be obtained by scanning electron microscopy (SEM) analysis. A crystal habit regulation scheme for hollow tubular VIP crystal has been reported by Sun et al 15 The SEM photographs shown in Figure 6 revealed a cubic VIP crystal with multiple types of cavities on the surface of the crystal. These features shared by Figure 6a,b suggested that the isolated cavities on the crystal plane usually appear at the junction of the crystal face, and the scanning electron microscope image shows that the size of the exposed cavities entrance reached 10−20 μm.…”
Section: Resultsmentioning
confidence: 81%
“…12−14 It is known that VIP crystalline products contained several crystal habits and extraordinary crystal defects. Sun et al 15 designed a specific antisolvent crystallization protocol to obtain a tubular VIP crystal and proposed the theoretical mechanisms for its formation. However, studies on the formation mechanism of VIP crystal defects and the regulation of key influencing factors have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, it is known that the polymorphism, morphology, and particle size can work together to affect the dissolution behavior of a solid drug. 51,52 As the particle size was controlled to the same level for all the samples by sieving before the dissolution testing, the different polymorphic forms and different morphologies are possible reasons for the better dissolution behavior of AXI-GA·H 2 O than AXI-GA I .…”
Section: Resultsmentioning
confidence: 99%
“…Antisolvent crystallization is an essential separation and purification technology in the manufacturing of fine chemicals , and pharmaceutical crystals. By avoiding high-temperature operations, antisolvent crystallization is suitable for heat-sensitive materials with low energy consumption. Also, the final product can be easily regulated by adjusting the operating parameters and solution/antisolvent system. , While the traditional approach of antisolvent crystallization usually involves batch droplets and mixing of the antisolvent, this operation commonly induces a local high supersaturation degree and explosive nucleation, which easily result in broad crystal size distribution and undesired particle morphology. The mixing rate and supersaturation distribution cannot meet the stable nucleation requirement of the scale-up operation . Thus, the accurate mass transfer and supersaturation control at the antisolvent–solvent mixing interface are the eternal concerns to hinder the exceeding local supersaturated concentration and explosive nucleation. …”
Section: Introductionmentioning
confidence: 99%